The work–recovery cycle of kidney strain and inflammation in sugarcane workers following repeat heat exposure at work and at home - Rebekah A. I. Lucas; Erik Hansson; Bethany D. Skinner; Esteban Arias-Monge; Catharina Wesseling; Ulf Ekström; Ilana Weiss; Zoey E. Castellón; Scarlette Poveda; Fatima I. Cerda-Granados; William Jose Martinez-Cuadra; Jason Glaser; et al. (European Journal of Applied Physiology, 2025)
Purpose To examine heat exposure at work and home and the work–recovery cycle and temporal variation of kidney strain, muscle injury and inflammation biomarkers in sugarcane workers. Methods 20 male sugarcane workers (age: 33 ± 7 years) with a workplace Rest.Shade.Hydration (RSH) intervention were observed over 4 days, at the end (18 h post-shift recovery) and beginning of a work week (42 h post-shift recovery). Measures included work intensity (heart rate), gastro-intestinal temperature, estimated body core temperature (using heart rate), fluid consumption, pre- and post-work blood and urine samples, physical activity (accelerometery) away from work, plus ambient heat exposure at work and home. Results On workdays, workers awakened at approx. 02:40 after 5 h sleep in ~ 30 °C. Across work shifts, daily average WBGT ranged from 26 to 29 °C (cooler than normal) and average workload intensity ranged from 55 to 58%HR max . Workers reported consuming ~ 8 L of water and ~ 4 × 300 mL bags of electrolyte fluid each day. Serum creatinine, cystatin C and creatine phosphokinase markedly increased post-work and decreased during recovery; serum potassium did the opposite (all p < 0.01). Biomarker concentration changes were similar between recovery periods (18 h vs. 42 h; all p > 0.27). C-reactive protein was the highest at the end of the work week ( p = 0.01). Conclusion Despite RSH intervention, cross-shift kidney strain was marked (recovering overnight) and systemic inflammation increased over the work week. Thus, biomonitoring of kidney function in occupational populations should be performed before a work shift at any point in the work week. This is essential knowledge for field studies and surveillance.